2005
DOI: 10.1159/000085922
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Sized Transurethral Catheters on Pressure-Flow Studies in Women with Lower Urinary Tract Symptoms

Abstract: Introduction: The study evaluates the impact of three different sized (4.5-, 6- and 7-Fr) catheters on pressure-flow studies in women undergoing urodynamic evaluation for lower urinary tract symptoms. Material and Methods: 60 women referred for the evaluation of lower urinary tract symptoms were enrolled in this randomized controlled study. Patients were divided into two groups (A and B) of 30 women each. The patients underwent non-invasive free-flow uroflowmetry with determination of post-void residual urine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…21 Interestingly, Scaldazza and Morosetti have also confirmed that the use of smaller catheters (4.5 Fr) resulted in a decrease P det Q max in comparison to bigger ones (7 Fr). 16 This effect on the P det Q max has also been studied in men by Zhao and colleagues. 22 These authors concluded that the use suprapubic catheters lowered the P det Q max by more than 10 cmH 2 0 in comparison of transurethral catheters.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…21 Interestingly, Scaldazza and Morosetti have also confirmed that the use of smaller catheters (4.5 Fr) resulted in a decrease P det Q max in comparison to bigger ones (7 Fr). 16 This effect on the P det Q max has also been studied in men by Zhao and colleagues. 22 These authors concluded that the use suprapubic catheters lowered the P det Q max by more than 10 cmH 2 0 in comparison of transurethral catheters.…”
Section: Discussionmentioning
confidence: 77%
“…15 This was confirmed by Scaldazza and Morosetti. 16 They evaluated the impact of 3 different sized catheters (4.5, 6 and 7 Fr). They demonstrated that all 3 may obstruct micturition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher values for Q max seen with AMB (on average 33%) might be explained at least partially by the presence of both 4Fr and 10Fr urethral catheters during CONV. Some evidence in support of this contention comes from intra-individual comparison of Q max with and without the presence of a urodynamic measurement catheter with studies in healthy (12) and symptomatic women (13)(14)(15) showing relative differences of between 28% and 64% using 6Fr, 7Fr and 9Fr catheters.…”
Section: Resultsmentioning
confidence: 99%
“…The transurethral catheter used to fill the bladder and to record the pressure may produce some effects on the physiology of voiding: irritative effect, bladder outlet obstruction. These potential effects have been few studied in women; [1][2][3][4][5] in addition the findings are controversial.…”
Section: Introductionmentioning
confidence: 99%